2014
DOI: 10.15567/mljekarstvo.2014.0301
|View full text |Cite
|
Sign up to set email alerts
|

Linear vs. piecewise Weibull model for genetic evaluation of sires for longevity in Simmental cattle

Abstract: This study was focused on genetic evaluation of longevity in Croatian Simmental cattle using linear and survival models. The main objective was to create a genetic model that is most appropriate to describe the longevity data. Survival analysis, using piecewise Weibull proportional hazards model, used all information on the length of productive life including censored as well as uncensored observations. Linear models considered culled animals only. The relative milk production within herd had a highest impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
3
9
1
Order By: Relevance
“…the environmental and genetic effects. Our estimates of Weibull parameters, the shape parameter (ρ) 2.25 and the intercept (ρlogλ) −15.14, were in the range of values reported by Sasaki (2013) for longevity traits in dairy cattle, and were similar to results obtained for Simmental populations (Jovanovac et al 2013;Raguz et al 2014). Such values of these parameters (with ρ > 1) demonstrate the age-linked increase of cows' culling risk.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…the environmental and genetic effects. Our estimates of Weibull parameters, the shape parameter (ρ) 2.25 and the intercept (ρlogλ) −15.14, were in the range of values reported by Sasaki (2013) for longevity traits in dairy cattle, and were similar to results obtained for Simmental populations (Jovanovac et al 2013;Raguz et al 2014). Such values of these parameters (with ρ > 1) demonstrate the age-linked increase of cows' culling risk.…”
Section: Discussionsupporting
confidence: 84%
“…The equivalent heritability (0.09; Table 2) accounting for the level of censoring (Eq. 4b), was higher than heritabilities between 0.06 and 0.08 reported in other studies of Simmental cattle longevity (Jovanovac et al 2013;Strapakova et al 2013;Raguz et al 2014). The moderate heritability supports the possibility of selection for functional longevity in Polish Simmentals.…”
Section: Discussionmentioning
confidence: 57%
“…Increase in sire breeding values is distinguished. Genetic trends of LPL sires of two breeds in Slovakia were similar in compare with many authors (van Doormaal, 2009;Raguž et al, 2014;Egger-Danner et al, 2015;Stanojević et al, 2018;Morek-Kopeć et al, 2017). The negative genetic trends in functional longevity found Imbayarwo-Chikosi et al (2017) in South Africa Holstein cattle and Jenko et al (2013) in Slovenian Brown cattle, which could have been resulting from intense selection on high milk production.…”
Section: Discussionsupporting
confidence: 83%
“…The holstein sire variance obtained in Weibull model was similar as stated Sewalem et al (2005) (0.046) and Imbayarwo-Chikosi et al (2017) (0.047). Raguž et al (2014) and Morek-Kopeć and Zarnecki (2017) found higher Simmental sire variance in compare with our results (0.03 and 0.069).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation